2005
DOI: 10.1159/000083639
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Status Affects Rat Liver Regeneration After Partial Hepatectomy by Regulating Cell Cycle and Apoptosis

Abstract: In rats, various growth factors and hormones, as well as partial hepatectomy (PH) are able to trigger the proliferative response of hepatocytes. Although recent evidence highlights the important role of thyroid hormones and thyroid status in regulating the growth of liver cells in vitro and in vivo models, the mechanism involved in the pro-proliferative effects of thyroid hormones is still unclear. Here we have investigated how in rats made hypo- and hyperthyroid after prolonged treatment respectively with pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 43 publications
(44 reference statements)
6
35
0
Order By: Relevance
“…Alisi et al (2005) demonstrated that hyperthyroidism increased the expression of cyclins D1, E, and A and decreased the expression of p16/INK4A and p27/KIP1 in a rat model of liver regeneration; this study also showed that hypothyroidism resulted in the reduced expression of these cyclins, as well as the increased expression of p16/INK4A, p27/KIP1, and p53.…”
Section: Figuresupporting
confidence: 56%
See 1 more Smart Citation
“…Alisi et al (2005) demonstrated that hyperthyroidism increased the expression of cyclins D1, E, and A and decreased the expression of p16/INK4A and p27/KIP1 in a rat model of liver regeneration; this study also showed that hypothyroidism resulted in the reduced expression of these cyclins, as well as the increased expression of p16/INK4A, p27/KIP1, and p53.…”
Section: Figuresupporting
confidence: 56%
“…TH-mediated regulation of cyclin-CDK complexes leading to cell arrest (Toms et al 1998) or cell differentiation (Ballock et al 2000) has also been demonstrated. Alisi et al (2005) showed in vivo that hyperthyroidism increases the levels of cyclins D1, E, and A and the activity of cyclin-CDK complexes, and decreases the levels of CDKIs, such as p16/INK4A (CDKN2A) and p27/KIP1 (CDKN1B). They also demonstrated that hypothyroidism induces contrary effects and that THs modulate the expression of the tumor suppressor genes p53 (Trp53) and p73 (Trp73), both involved in apoptosis and growth arrest.…”
Section: Introductionmentioning
confidence: 99%
“…It is also well established that thyroid hormone can increase the growth of the liver after PH because injection of T3 into mice after PH increases the rate of liver regeneration (Moro et al, 2004;Alisi et al, 2005). It does not appear that CAR directly regulates the levels of T3, although ability of CAR to regulate the levels of rT3 may be akin to regulation of T3 itself.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a possible involvement of pronerve growth factor-p75 neurotrophin receptor pathway in hypothyroidism-enhanced apoptosis has been demonstrated during rat cortical development (Kumar et al, 2006). In addition, it has been demonstrated that hypothyroidism increases the level of p73, a protein involved in apoptosis, during rat liver regeneration (Alisi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%